Pollination ecology of Rodriguezia granadensis (Orchidaceae) - Ospina-Calderón, Nhora H.; Duque-Buitrago, Carol A.; Tremblay, Raymond L.; Otero, J. Tupac (Lankesteriana: International Journal on Orchidology, 2015)
In this paper we describe the phenotypic variation and pollination ecology of the twig orchid epiphyte Rodriguezia granadensis. The species presents flower color polymorphism (pink to white), suggesting that different color forms might be pollinated by different pollinators. To evaluate this hypothesis, one hundred plants were monitored in the field and their flowering phenology and color polymorphism was noted, two peaks of flowering were noted over the year. We evaluated the reproductive success (pollinaria removal and fruit set) and the visit of potential pollinators to both morphs. Fruit production by autogamy, geitonogamy, xenogamy, and emasculation were compared. Sugar concentration in the nectar was measured with a refractometer. Potential pollinators, euglossini bees, were attracted using methyl salicylate and eugenol. We evidenced that R. granadensis is pollinated by nectar-foraging euglossine bees. The fluctuation in nectar production and the scarce reproductive success among individuals suggests that the orchids may employ an attraction-deceit system as a self-mimetic or a diffuse rewarding phenomenon.